2005
DOI: 10.1590/s1516-35982005000300015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de níveis de proteína bruta e de energia metabolizável na dieta sobre o desempenho de codornas de postura

Abstract: RESUMO -Objetivou-se, neste experimento, avaliar o efeito de diferentes níveis de proteína bruta (PB) e de energia metabolizável (EM) sobre o desempenho de codornas de postura. Foram utilizadas 672 codornas japonesas (Coturnix coturnix japonica) a partir de 42 dias de idade, durante 168 dias de produção, dividido em seis períodos de 28 dias cada, distribuídas em delineamento inteiramente casualizado, em arranjo fatorial de 4 x 4 (proteína x energia), com seis repetições de sete aves por unidade experimental. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
0
31

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 10 publications
6
1
0
31
Order By: Relevance
“…Due to the low feed intake observed in severe restriction levels, quails started to drastically decrease egg production from the third level of feed supply (75% ad libitum), behavior similar to that reported by Rabello et al (2004) Table 2 -Performance of Japanese quails under different levels of feed supply protein consumption (Pinto et al, 2002). This correlation effect has been observed between protein intake and egg weight, since 5.22 g/bird/day/ of protein intake and 11.67 g of egg weight were observed in this research for quails fed ad libitum, while Freitas et al (2005) found 4.85 g/bird/day and 10.37 g eggs in hens fed ad libitum on 20% crude protein.…”
Section: Resultssupporting
confidence: 76%
“…Due to the low feed intake observed in severe restriction levels, quails started to drastically decrease egg production from the third level of feed supply (75% ad libitum), behavior similar to that reported by Rabello et al (2004) Table 2 -Performance of Japanese quails under different levels of feed supply protein consumption (Pinto et al, 2002). This correlation effect has been observed between protein intake and egg weight, since 5.22 g/bird/day/ of protein intake and 11.67 g of egg weight were observed in this research for quails fed ad libitum, while Freitas et al (2005) found 4.85 g/bird/day and 10.37 g eggs in hens fed ad libitum on 20% crude protein.…”
Section: Resultssupporting
confidence: 76%
“…Murakami et al (1993), Pinto et al (2002) e Freitas et al (2005) também verificaram aumento linear do consumo de ração com a redução do nível de energia para codornas japonesas. Desta forma, pode-se inferir que o comportamento alimentar de codornas é semelhante ao de galinhas poedeiras, que alteram o consumo de ração de acordo com o nível de energia da dieta (Murakami, 1993;Belo et al, 2000;Garcia et al, 2000;Pinto et al, 2002).…”
Section: Resultsunclassified
“…De acordo com Yamane et al (1980) e o NRC (1994), o consumo diário de energia de codornas japonesas para máxima produção deve ser de 63 a 75 kcal/ave/dia. Freitas et al (2005), avaliando vários níveis de EM para codornas japonesas, concluíram que houve ingestão média de 66 kcal/ave/dia. O consumo de proteína bruta não diferiu (P>0,05) entre as aves.…”
Section: Resultsunclassified
See 2 more Smart Citations